2016
DOI: 10.21836/pem20160110
|View full text |Cite
|
Sign up to set email alerts
|

The role of PGE2 and PGF2a in follicle wall rupture and their implications in the development and treatment of luteinized unruptured follicles

Abstract: Summary:The article summarizes the results of several studies, which highlight the relevance of prostaglandins E2 (PGE2) and F2 (PGF2a) during the ovulatory process in mares and their implication in the pathogenesis of luteinized unruptured follicles. Following the preovulatory luteinizing hormone (LH) surge, the two prostaglandins are synthesized in granulosa cells. They subsequently trigger a cascade of events that lead to ovulation. The exogenous administration of intrafollicular PGE2 and PGF2a can induce f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Interestingly, it has been shown that in the equine, COX2 gene expression in granulosa cells is a long molecular process, when compared to other species; appearing to be switched on approximately 30 h after the administration hCG for ovulation induction ( Boerboom & Sirois 1998 ). Prostaglandin synthesis, PGF 2α and PGE 2 have a role in follicular wall rupture and can be detected locally in equine follicular fluid ( Cuervo-Arango & Martìnez-Bovì 2016 ); no systemic increase in either of these lipids has been detected at ovulation. As oocyte expulsion must occur for natural fertilisation to take place, the interplay of many lipid hormones, at both local and systemic levels, is essential.…”
Section: Exploration Of Lipid Pathways In Equine Cyclicity and Early ...mentioning
confidence: 99%
“…Interestingly, it has been shown that in the equine, COX2 gene expression in granulosa cells is a long molecular process, when compared to other species; appearing to be switched on approximately 30 h after the administration hCG for ovulation induction ( Boerboom & Sirois 1998 ). Prostaglandin synthesis, PGF 2α and PGE 2 have a role in follicular wall rupture and can be detected locally in equine follicular fluid ( Cuervo-Arango & Martìnez-Bovì 2016 ); no systemic increase in either of these lipids has been detected at ovulation. As oocyte expulsion must occur for natural fertilisation to take place, the interplay of many lipid hormones, at both local and systemic levels, is essential.…”
Section: Exploration Of Lipid Pathways In Equine Cyclicity and Early ...mentioning
confidence: 99%